The Incapacitation Effect of Incarceration: Evidence From Several Italian Collective Pardons - Alessandro Barbarino
Incarceration of criminals reduces crime through two main channels, deterrence and incapac- itation. Because of a simultaneity between crime and incarceration–arrested criminals increase the prison population–it is difficult to measure these effects. This paper estimates the incapaci- tation effect on crime using a unique quasi-natural experiment, namely the recurrent collective pardoning between 1962 and 1995 of up to 35 percent of the Italian prison population. Since these pardons are enacted on a national level, unlike in Levitt (1996), we can control for the endogeneity of these laws that might be driven by criminals’ expectations: it is optimal to com- mit crimes shortly before a collective pardon gets enacted. This effect represents a deterrence effect, which, if not properly controlled for, would bias our IV estimates towards zero. The incapacitation effect is large and precisely estimated. The elasticity of crime with respect to prison population ranges, depending on the type of crime, between 0 and 49 percent. These numbers are increasing during our sample period, which suggests that habitual criminals are now more likely to be subject to pardons than in the past. A benefit-cost analysis suggests that pardons, seen as a short term solution to prison overcrowding, are inefficient.Crime, Pardon, Amnesty, Deterrence, Incapacitation